Multiplex degenerate four-wave mixing in a flame. - Ewart, P; Snowdon, P (1990)
The principle of multiplex degenerate four-wave mixing (DFWM) is demonstrated by recording, with a single laser shot, DFWM signals from both D lines of atomic sodium in a seeded flame. Applications of the technique for singleshot temperature measurements for combustion diagnostics are discussed.